Fish Oil Microencapsulation as Omega-3 Fatty Acids Fortification Material for Cream of Crab Soup - Santiara Putri Pramestia; Bambang Riyanto; Wini Trilaksani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Omega-3 fatty acids have important roles in improvement of intelligent and healthof human. Microencapsulation of fish oil as source of omega-3 fatty acids is an effort tomaintain flavor, aroma, stability, and also to successfully transfer bioactive componentfrom the fish oil as fortification material for foods or medicines. Improvement of instantcrab cream soup enriched with fish oil as source of omega-3 fatty acid has never beenconducted before. The purpose of this research was to improve microencapsulationmethod for fish oil as source of omega-3 fatty acids as fortification material for instantcream of crab soup. Microencapsulation methods in this research are homogenizationand spray drying. The results showed that the best microcapsule was obtained fromhomogenization treatment for 10 minutes with efficiency of 90.41±0.64%. The shape ofthe obtained microcapsule was spherical with average size of 6.52 μm, with induction timeup to 26.09±0.01 hours. The best cream of crab soup formula was at fish oil microcapsule concentration of 3.30%, with 8.19% daily value of omega-3, inclusion 11.32% of EPA andDHA at serving size of 17.56 gram.Keywords : Crab, fish oil, fortification, instant cream soup, microencapsulation, omega-3fatty acids